Palliative dental care for head and neck cancer patients in Intensive Care Units: an integrative review of the literature (Research, Society and Development, 2021)
Palliative care dentistry is described as the study and management of patients with active, progressive and very advanced disease, in whom the oral cavity has been compromised by the disease directly or by its treatment. The head and neck oncology patients that are submitted to ICU in most cases already have the neoplasm in more advanced stages of the disease. Antineoplastic therapies and the advanced stage of head and neck cancer itself may lead patients to progressive or sudden oral deterioration. Considering these aspects, the aim of this study was to establish which are the palliative dental care in patients with head and neck cancer who are in intensive care units. This is a bibliographic study, basic, with integrative analysis, for which the databases platforms Pubmed (MEDLINE), Scielo and EBSCO were used, including articles from the year 2010, besides classic articles, where the following descriptors were searched: "dental care", "intesive care units", "head and neck neoplasms", "palliative care" besides the Boolean descriptor "AND". The literature shows that the oral conditions that most affect these patients are xerostomia, mucositis and candidiasis among others. We conclude then that the presence of the dental surgeon in the ICU is an important factor for these patients with regard to the maintenance of oral structures and oral palliative treatments that aim to improve pain among other functions.